Lost Historical Bridges of Malatya: Kırkgöz and Deir Massiah - Cakar, Enver; Sen, Korkmaz; Kisa, Yavuz; Olgun, Tuba Nur; Sahin, Murat; Toprak, Ahmet (Istanbul Univ, Research Inst Turkology, Dept Art History, 2025)
Malatya, which is located atthe intersection pointofthe roads reachingfrom Mesopotamia to the interior of Anatolia and the Black Sea, lies in a geography rich in water resources. The Tohma Stream, which originates in Uzunyayla, reaches Malatya by incorporating the water of G & uuml;r & uuml;n, and from there flows into the Euphrates River. Other waters, especially Sultansuyu and Derme Creek (Deir Massiah) in Malatya, also flow into the Tohma Stream. Large and small bridges were built during and before the Ottoman period to provide transportation over these waters, which played an important role in the development of Malatya agriculture. The most important of these is the K & imath;rkg & ouml;z Bridge, which provides transportation between Sivas-Malatya-Diyarbak & imath;r and Malatya-Erzincan-Erzurum. The Deir Massiah Bridge is also one of the important historical bridges of the city. However, none of these bridges has survived to this day. The aim of this study is to reveal the importance of K & imath;rkg & ouml;z Bridge, which is located on historical transport networks, and the Deir Massiah Bridge, which also served as an aqueduct, in terms of architecture, transport and economic history. The main sources of the study are Ottoman archive documents, Ottoman yearbooks, travelogues, periodicals and research and studies on the subject.
Malatya’nın Yitik Tarihi Köprüleri: Kırkgöz ve Deyr-i Mesih
Keywords: Malatya; K & imath;rkg & ouml;z Bridge; Deir Massiah Bridge; Tohma Stream; historical bridges